BN-embedded eleven-ring fused heteroaromatics: Synthesis, optoelectronic properties and fluoride susceptibility. (June 2020) - Huang, Huaxi; Chen, Di; Li, Fei; Xing, Zhixi; Zhao, Jingjing; Wu, Di; Liang, Guijie; Xia, Jianlong
Abstract: π-conjugated aromatics have received broad research interests in the past decades due to their wide applications. Expanding the π-conjugated backbone can lengthen the absorption and emission bands. In addition, incorporating heteroatoms into the polycyclic aromatic hydrocarbons (PAHs) provides a versatile avenue to fine-tuning their optoelectronic properties and stabilities. In this study, BN-embedded eleven-ring fused heteroaromatics BNAT1 was synthesized using a concise synthetic route, and a mono-fused byproduct BNAT2 was obtained as well. The optoelectronic properties of BNAT1 and BNAT2, as well as their fluoride susceptibility have been investigated. Both compounds showed good stability in spite of the existence of multi-ring-fused backbone. Moreover, BNAT1 displayed selectively colorimetric and turn-off fluorescence response to fluoride over other relevant anions. Graphical abstract: Image 1 Highlights: The BN-embedded eleven-ring fused heteroaromatics BNAT1 was synthesized using a concise synthetic route. BNAT1 has excellent air and light stability. BNAT1 displayed selectively colorimetric and turn-off fluorescence response to fluoride.